Species and spatial variation in the effects of sea ice on Arctic seabird populations. Issue 11 (2nd August 2021) - Descamps, Sébastien; Ramírez, Francisco
Abstract: Aim: The Arctic is warming rapidly, and sea ice is disappearing. This is expected to have profound effects on Arctic wildlife. However, empirical evidence that this decline in sea ice is associated with a decline in Arctic wildlife populations is lacking. Location: Svalbard Archipelago. Methods: Using long‐term time series data (1988–2018) from two fjords in West Spitsbergen (Svalbard), we tested whether or not sea ice concentration was associated with the population size of two of the most common Arctic seabirds, the Brünnich's guillemot ( Uria lomvia ) and black‐legged kittiwake ( Rissa tridactyla ). Results: We found that the size of guillemot and kittiwake colonies has declined on Svalbard from the mid‐1990s onwards, though the shapes of these trajectories were not linear and kittiwake colony size has stabilized or even increased in recent years. sea ice concentration in West Spitsbergen also declined during the study period. Independent of these long‐term trends, sea ice concentration was positively and significantly associated with seabird colony size with a 2‐year lag, though variations in sea ice explained only a small proportion of the changes in colony size. One likely mechanism linking sea ice and seabird population size involves changes in the food chain, with poor sea ice conditions in a given year leading to low food availability 2 years later. This would affect breeding probability and hence colony size for kittiwakes and guillemots. This relationship between sea ice and colony size was the same in both fjords for guillemots. In the case of kittiwakes, it was not apparent in the fjord where productive glacier fronts, intensely used by kittiwakes to forage, may have buffered the effects of changes in sea ice. Main conclusions: Our study provides evidence that the ongoing decline in Arctic sea ice plays a role in Arctic seabird population trajectories. However, sea ice disappearance on the breeding grounds was likely not the main driver of changes in seabird populations.